Afasia global. Documentación de 3 años tratamiento desde la fase aguda a crónica - Venegas-Mahn, Maccarena Paz (Revista Hospital Clínico Universidad de Chile, 2022)
Aphasia as a sequel to stroke is present between 14-28% worldwide and in 20% in the Chilean population. The most serious form is called global aphasia, with a severe alteration of the comprehensive and expressive language, with a poor communicative prognosis and quality of life for the patient and families. The objective of this case is to describe the evolution of a person with global aphasia from the acute phase to 3 years of speech therapy treatment, who achieved a successful evolution of their language, communication and quality of life. This paper presented anamnestic data of the case, initial and systematic evaluation of linguistic functions and impact on quality of life, and the results that document its progress in 3 years. Also, this case is described dynamic person-centered treatment and methodology to start in the acute phase with severe compromise (aphasic cocient 6/100 Cutoff 93.8) and after 3 years improve to mild-moderate aphasia (76/100 points). Progress in vitality, communication, physical and psychosocial aspects and the mean quality of life score are described quantitatively.